South African critical care nurses' views on end-of-life decision-making and practices - Langley, G.; Schmollgruber, S.; Fulbrook, P.; Albarran, J.; Latour, Jos (2014)
Background: Care of patients at the end-of-life (EOL) may be influenced by the experiences, attitudes and beliefs of nurses involved in their direct care. Aim: To investigate South African critical care nurses' experiences and perceptions of EOL care. Design: Cross-sectional survey. Methods: South African critical care nurses completed a modified version of the ‘VENICE’ survey tool. Data were collected concerning: attitudes towards EOL care; involvement in EOL decision-making; and beliefs about EOL practices. Results: Of 149 surveys distributed, 100 were returned (response rate 67%). Seventy-six percent stated that they had had direct involvement in EOL care of patients, but a minority (29%) had participated in EOL decision-making processes. Whilst most nurses (86%) were committed to family involvement in EOL decisions, less than two thirds (62%) reported this as routine practice. When withdrawing treatment, around half (54%) of the respondents indicated they would decrease the inspired oxygen level to room air, and the majority (84%) recommended giving effective pain relief. Continued nutritional support (84%) and hydration (85%) were advocated, with most nurses (62%) indicating that they were against keeping patients deeply sedated. Most respondents (68%) felt patients should remain in intensive care at the end of life, with the majority (72%) supporting open-visiting, no restriction on number of family members visiting (70%), and the practising of religious or traditional cultural EOL rituals (93%). Conclusions: The involvement of Johannesburg critical nurses in EOL care discussions and decisions is infrequent despite their participation in care delivery and definite views about the process.